Determination of Spatial Chromium Contamination of the Environment around Industrial Zones - Dereje Homa; Ermias Haile; Alemayehu P. Washe (International Journal of Analytical Chemistry)
This study was conducted to determine the spatial levels of chromium contamination of water, agricultural soil, and vegetables in the leather tanning industrial areas using spectrophotometric methods. The results showed elevated accumulation of total Cr ranging from 10.85±0.885 mg/L to 39.696±0.326 mg/L, 16.225±0.12 mg/Kg to 1581.667±0.122 mg/Kg, and 1.0758±0.05348 mg/Kg to 11.75±0.206 mg/Kg in water, agricultural soil, and vegetable samples, respectively. The highest levels of chromium (VI) found from the speciation study were 2.23±0.032 mg/Kg and 0.322±0.07 mg/L in soil and water samples, respectively, which decreased with distance from the tannery. Among the vegetables, the highest load of Cr(VI) was detected in onion root (0.048±0.065 mg/Kg) and the lowest (0.004±0.007 mg/Kg) in fruit of green pepper. The detected levels of Cr in all of the suggested samples were above the WHO permissible limits. The variations of the levels Cr(III) and Cr(VI) contamination of the environment with distance from the tannery were statistically significant (p=0.05). Similarly, significant difference in the levels of Cr among the tested vegetables was recorded. The levels increased with decreasing distance from the effluent channel.